Brominated Bisindole Alkaloids from the Celtic Sea Sponge Spongosorites calcicola - Jennings, L. K.; Khan, N. M. D.; Kaur, N.; Rodrigues, D.; Morrow, C.; Boyd, A.; Thomas, O. P. (Molecules, 2019)
As part of an ongoing program to identify new bioactive compounds from Irish marine bioresources, we selected the subtidal sponge Spongosorites calcicola for chemical study, as fractions of this species displayed interesting cytotoxic bioactivities and chemical profiles. The first chemical investigation of this marine species led to the discovery of two new bisindole alkaloids of the topsentin family, together with six other known indole alkaloids. Missing the usual central core featured by the representatives of these marine natural products, the new metabolites may represent key biosynthetic intermediates for other known bisindoles. These compounds were found to exhibit weak cytotoxic activity against HeLa tumour cells, suggesting a specificity towards previously screened carcinoma and leukaemia cells.